E-161 Optimal parameter for predicting final infarct volume and outcome after complete recanalization of medium vessel stroke. (23rd July 2022) - Guenego, A; Lubicz, B
Abstract : Background and Purpose: We sought to assess the optimal parameter and best threshold on baseline computed-tomography-perfusion (CTP) to predict final-infarct-volume, infarct progression and clinical outcome after successful endovascular recanalization of acute ischemic stroke (AIS) with primary distal, medium vessel occlusions (DMVO). Methods: We performed a retrospective analysis of consecutive AIS patients who underwent an initial CTP, were successfully recanalized by thrombectomy for DMVO and underwent a follow-up MRI. We evaluated the correlation of baseline infarct and TMax volumes with final-infarct-volume and infarct progression between CTP and follow-up MRI, as-well-as 3 months good clinical outcome (modified Rankin Scale score of 0 to 2). Results: Between January 2018 and January 2021, 38 patients met inclusion criteria (76% [29/38] female, median age 75 [66–86] years). Median final-infarct-volume and infarct progression were respectively, 8.4 mL [IQR: 5.2–44.4] and 7.2 mL [IQR: 4.3–29.1]. TMax>10sec volume had the strongest correlation with final-infarct-volume and infarct progression (respectively, r=0.831 and r=0.771, p<0.0001) as-well-as good clinical outcome (-0.5, p=0.001). Higher baseline TMax>10sec volumes increased the probability of higher final-infarct-volume and infarct progression (respectively, r²=0.690, coefficient=0.83 [0.64–1.00], p<0.0001 and r²=0.595, coefficient=0.77 [0.56–0.98], p<0.0001), whereas it decreased the probability of 3 months good clinical outcome (ODDs ratio = -0.67 [-1.17 to -0.18], p=0.008). ROC curves identified a TMax>10sec volume <33mL as the optimal threshold to predict a low final-infarct-volume (AUC=0.802), low infarct progression (AUC=0.735) and good clinical outcome (AUC=0.786). Conclusion: TMax>10sec volume on baseline CTP predicts final-infarct-volume and progression as-well-as clinical outcome after MT recanalization for AIS with DMVO. Disclosures: A. Guenego: None. B. Lubicz: None.